2014
DOI: 10.1262/jrd.2013-102
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Improves the Mitochondrial Function and Fertilization Outcome of Bovine Oocytes

Abstract: The aim of the present study was to address the effect of resveratrol-mediated upregulation of sirtuin 1 (SIRT1) during oocyte maturation on mitochondrial function, the developmental ability of oocytes and on mechanisms responsible for blockage of polyspermic fertilization. Oocytes collected from slaughterhouse-derived ovaries were cultured in TCM-199 medium supplemented with 10% FCS and 0 or 20 µM resveratrol (Res). We examined the effect of Res on SIRT1 expression in in vitro-matured oocytes (Exp 1); fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 39 publications
8
58
0
3
Order By: Relevance
“…Resveratrol, a natural antioxidant, can enhance oocyte quality in diverse mammalian species (Lee, et al, 2010, Liu, et al, 2013, Mukherjee, et al, 2014). In bovine and porcine oocytes, resveratrol activates Sirtuin 1, which in turn promotes mitophagy to eliminate damaged mitochondria, increases mitochondrial number, and improves mitochondrial function (Sato, et al, 2014b, Takeo, et al, 2014). Resveratrol also enhances cumulus cell function, oocyte maturation, decreases ROS in bovine oocytes, and increases glutathione concentration in oocytes (Wang, et al, 2014).…”
Section: Interventions To Reduce Impact Of Er Stress Responsementioning
confidence: 99%
“…Resveratrol, a natural antioxidant, can enhance oocyte quality in diverse mammalian species (Lee, et al, 2010, Liu, et al, 2013, Mukherjee, et al, 2014). In bovine and porcine oocytes, resveratrol activates Sirtuin 1, which in turn promotes mitophagy to eliminate damaged mitochondria, increases mitochondrial number, and improves mitochondrial function (Sato, et al, 2014b, Takeo, et al, 2014). Resveratrol also enhances cumulus cell function, oocyte maturation, decreases ROS in bovine oocytes, and increases glutathione concentration in oocytes (Wang, et al, 2014).…”
Section: Interventions To Reduce Impact Of Er Stress Responsementioning
confidence: 99%
“…Also examined was whether potassium bromate-induced mitochondrial aggregation could be rescued by the addition of the antioxidant, resveratrol, which has been suggested to be useful in IVM and embryo culture systems. Several studies have reported improvements with resveratrol: the fertilization rate was increased by a reduction of active oxygen, 28 the pregnancy rate was increased by improved mitochondrial function, 21 and fertility and embryo developmental capacities were improved by an increased number of active mitochondria, leading to better-quality oocytes. 29 Collectively, these reports suggest that resveratrol improves mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that high doses of potassium bromate decreased the percentage of oocytes at the metaphase II (MII) stage and increased abnormal mitochondrial distribution. Furthermore, as the efficacy of resveratrol as an antioxidant has been reported, it was investigated whether resveratrol could improve the oxidizing actions that had been elicited by potassium bromate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidants can improve oocyte quality and enhance embryo development (Huang et al, 2013; Ideta et al, 2012; Orsi and Leese, 2001; Takeo et al, 2014; Wang et al, 2014a) and also protect against peroxide-induced damage (Yu et al, 2014) and other stress induced damage (Cebrian-Serrano et al ., 2013; Koyama et al ., 2012; Sakatani et al ., 2007) in embryos and oocytes (Devine et al ., 2012). Additionally, reduced glucose availability in vitro has long been recognized as beneficial to embryos (Chatot et al, 1989; Leese, 2012), although glucose starvation can actually increase ROS production and is not beneficial (Jansen et al, 2009).…”
Section: Activation and Inhibition Of Er Stress In Oocytes And Embmentioning
confidence: 99%